Three new species of the subfamily Bryophilinae from China (Lepidoptera, Noctuidae) - Han, Hui-Lin; Kononenko, Vladimir S.; Behounek, Gottfried (Zootaxa, 2011)
Three new species of the subfamily Bryophilinae (Victrix sinensis sp. n., Bryophila xizanga sp. n. and Stenoloba marinela sp. n.) are described from China. A new combination is proposed and lectotype designated for Victrix tripuncta Draudt, 1950, comb. n. Stenoloba speideli Kononenko & Ronkay, 2001 is reported for China for the first time. Checklists of the species of the genera Cryphia and Victrix occurring in China are presented.